Vehicle licensing and tolling application - Mabhena, Anold (Midlands State University, 2018)
This document provides a comprehensive overview of the Vehicle licensing and tolling application with the main aim of gathering and summarising facts, identifying as well as analysing alternatives thereby solving the problems faced at Zimbabwe National Roads Administration (ZINARA). Data gathering methodologies which include interviews, observations and questionnaires were used in identifying the problems currently being faced by the organisation. These included human errors and fraud as well as the poor handling of motorist inquiries. Their traditional way of issuing licenses was less effective since there was a limited motorist contribution in their system. The ever changing technology also led to the need for the android application to assist motorists and enhance their inquiry handling. Therefore the objectives of this research were to develop a system which allow the motorists to calculate their license fees on the application, remind the motorist when the motor vehicle is due for licensing and to create a platform that enable the motorists to make a calculation for the total fees required from a certain destination to the next. Android and MySQL technologies were used to develop the system meeting the objectives with the user requirements. In implementing the system several testing strategies were also used so as to mirror the user requirements and the system. User training was also done to the ZINARA employees and motorist so as to give them the understanding of the system. Maintenance schedules were also put in place after user training. Recommendations were also documented for further or future developments and this then will give an opportunity and ideas to the organisation in the future to improve the application.